Pengaruh Komunikasi Informatif tentang Seks dan Seksualitas terhadap Pengetahuan Remaja - Yulianita, Neni (Mediator, 2000)
This is an experimental study on the effects of the oral and written informative communication on sex and sexuality. The experiment was conducted at SMA in Bandung, the first class students being the experiment subjects. From the population (340 students), 78 students were picked up at random. The subjects were divided at random into three groups: the "oral" group (the listening group), the "written" group (the reading group), and the control group. Tests were given to the first group and the second group before and after the treatment, while test I and test II were given to the control group. The experiment aimed to test the following hypothesis: (1) There is a significant difference between the oral group and written group in their average knowledge on sex and sexuality; (2) There is a Significant difference between the male group and the female group exposed to both oral informative communication and written informative communication in their average knowledge on sex and sexuality; (3) There is a significant difference between the malegroup and the female group exposed to the oral informative communication, and between the male group and the female group exposed to the written informative communication in their average knowledge on sex and sexuality; (4) There is a significant difference between the male group exposed to the oral informative communication and the male group exposed to the written informative communication, and between the female group exposed to the oral informative communication and the female group exposed to the written informative communication in their average knowledge on sex and sexuality. Having been analyzed by the t and t tests, it was found that the second hypothesis was not accepted, while the others were accepted. It was also found that: (1) The oral informative communication was more effective than the written informative communication. (2) The oral informative communication was more effective on the male group, and the written informative communication was more effective on the female group.